Freestall design and management for cow comfort - John F. Smith; G. A. Jones; Joseph P. Harner (Kansas Agricultural Experiment Station Research Reports, 1997)
The design and management of freestall 4) air or vision. facilities are critical in maintaining cow comfort and high milk production. Dairy produc- Lunge Space ers should be conscious of the factors affecting cow comfort in freestall facilities. These The first reason a freestall may fail is lack factors include: ventilation, water availability, of lunge space. A cow needs forward or side feed availability, stall design, and stall bed- lunge space to maneuver in and out of the stall ding. Dairy producers should strive to have easily. There should be no obstructions in lactating cows standing to be milked; standing front of the stall above the brisket board if to eat; or lying down, chewing her cud, and cows are expected to lunge forward. If stall producing milk. Managers who take this length is limiting, consider wide dividing loops approach will improve both cow comfort and that allow cows to lunge to the side. The milk production.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Freestall; Management; Cow comfort